Effects of n-octanol as a fuel blend with biodiesel on diesel engine characteristics. (1st January 2019) - Ashok, B.; Nanthagopal, K.; Anand, Vivek; Aravind, K.M.; Jeevanantham, A.K.; Balusamy, Saravanan
Graphical abstract: Highlights: The blending of n-octanol with CIME has improved the engine performance. The increase of n-octanol in blends increase the ignition delay and in-cylinder pressure. Lower fraction of n-octanol in the blend is effective in reducing the NOx emission. Higher fraction of n-octanol in blends is beneficial in lowering CO and smoke. HC emission increases with the increase of n-octanol fraction. Abstract: Biodiesel can serve as possible alternate fuels in compression ignition engine as it leads to an effective reduction in consumption of fossil fuels. Moreover, it has been observed that biodiesel has the potential to reduce most exhaust emissions. The aim of the present study is to investigate the effect of n-octanol with Calophyllum Inophyllum biodiesel on compression ignition engine characteristics. Five different fuel blends are prepared by varying the concentration of n-octanol from 10% to 50% on a volume basis. It has been observed that the addition of n-octanol with biodiesel decreases the calorific value due to its inherent oxygen content. A mixed 6 × 5 level full factorial design with 3 replications was used for conducting the experiment. The statistical test by analysis of variance (ANOVA) revealed that CIME blend has the greater influence, contributing 71.3% to HC emission. The engine load has greatest influence of 98.88% to BTE followed by 98.77% to NOx, 95.74% to CO and 75% to peak pressure. The experimental results showed that the increase of n-octanol fraction in blends prolonged the ignition delay generating higher peaks of in-cylinder pressure and heat release rates during the premixed mode of combustion. Brake thermal efficiency has improved with the increase of n-octanol fraction up to 30% and then started decreasing with further increase of n-octanol in blends. Brake specific fuel consumption has reduced by about 20% with the increase of n-octanol fraction by 50%. Furthermore, the cooling effect produced by a lower fraction of n-octanol in the blend reduces the in-cylinder temperature resulting in lower NOx emissions. However, the poor ignition and evaporation characteristics of n-octanol has resulted in increase of CO and smoke emissions. HC emissions increase with the increase of n-octanol percentage due to the overleaning effect of the excess oxygen content in the n-octanol. The higher fractions of n-octanol is beneficial in lowering the CO and smoke emissions because of enhanced combustion due to the presence of excess oxygen. Overall, the addition of lower fraction of n-octanol with biodiesel has enhanced the performance output with the reduction of NOx emission with noteworthy penalty in CO and HC emissions.